2017
DOI: 10.1002/jssc.201700081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ion stacking in aqueous partition chromatographic processes

Abstract: It has been reported that ion enrichment phenomena are observed in liquid chromatographic processes with an aqueous mobile phase on the columns packed with nonionic materials. However, the mechanism of the ion enrichment is not at all well understood. In this study, we investigated the retention and enrichment behaviors of simple inorganic anions on a C18-bonded silica column and a cross-linked hydroxylated methacrylic polymer gel column with pure aqueous mobile phases containing various electrolytes. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Therefore it is desirable that the component anion of the background electrolyte has as small a distribution coefficient as possible in order to achieve higher enrichment of the target anions by PIEC stacking. In a previous study, 23 we demonstrated that sulfate ion exhibits the smallest distribution coefficient (D Na2SO4 SO4 = 0.32) among common inorganic anions, and that the overall stacking can be achieved for anions having the D A Na2SO4 larger than 1.78, such as nitrate, iodide, thiocyanate with the TSKgel G2500PWXL column (Vs = 3.42 mL), even when 5.00 mL of the sample solution was injected. We have thus adopted Na2SO4 as the background electrolyte to be added to the sample solution and validated the on-line PIEC ion stacking-IC method for the accuracy and reproducibility by determining nitrate ion in tap water.…”
Section: Determination Of Nitrate Ion In Tap Watermentioning
confidence: 90%
See 3 more Smart Citations
“…Therefore it is desirable that the component anion of the background electrolyte has as small a distribution coefficient as possible in order to achieve higher enrichment of the target anions by PIEC stacking. In a previous study, 23 we demonstrated that sulfate ion exhibits the smallest distribution coefficient (D Na2SO4 SO4 = 0.32) among common inorganic anions, and that the overall stacking can be achieved for anions having the D A Na2SO4 larger than 1.78, such as nitrate, iodide, thiocyanate with the TSKgel G2500PWXL column (Vs = 3.42 mL), even when 5.00 mL of the sample solution was injected. We have thus adopted Na2SO4 as the background electrolyte to be added to the sample solution and validated the on-line PIEC ion stacking-IC method for the accuracy and reproducibility by determining nitrate ion in tap water.…”
Section: Determination Of Nitrate Ion In Tap Watermentioning
confidence: 90%
“…We have shown that anionic solutes are excluded from the interior of the polymer gel particles in the TSKgel G2500PWXL column by the ion-exclusion effect of fixed anionic charges at an ionic strength of 1 mM or below, whereas the ion-exclusion effect is suppressed at 50 mM or above. 23 Accordingly, the concentration of the background electrolyte was set at 0.1 M.…”
Section: Determination Of Nitrate Ion In Tap Watermentioning
confidence: 99%
See 2 more Smart Citations
“…It has so far been reported that not only inorganic ions but also some small hydrophilic compounds such as urea show retention volumes obviously smaller than that of deuterium oxide on RPLC columns in some water–organic solvent and pure water eluent systems. 27 33 These phenomena have been interpreted with ion exclusion or size-exclusion mechanism assuming that hydrophilic molecules would have effective sizes much larger than their own by strong hydration. 29 32 We have shown that this specifically weak retention of small hydrophilic molecules should be attributed to their sensing of the interfacial solvated liquid layer.…”
Section: Introductionmentioning
confidence: 99%